Haemophilus aphrophilus endocarditis in pregnancy. - Anand, C M (1976)
The clinical and microbiological features of a case of Haemophilus aphrophilus endocarditis in pregnancy are described. The complicating effect of pregnancy on treatment and the difficulties in identifying the organism in the laboratory are discussed.